Is incidental gestational thrombocytopaenia really always safe for the neonate?. (August 2014) - Pourrat, O.; Valère, G.; Pierre, F.
Abstract It is widely admitted that neonates' platelet counts (PCs) are always normal in babies born to mothers with incidental gestational thrombocytopaenia. However, results of PC determinations at delivery have led us to wonder whether incidental gestational thrombocytopaenia is actually safe for the neonate under all circumstances, and to recommend that for every baby born to a mother with a pregnancy-associated thrombocytopaenia, even in the case of confirmed IGT, platelet counts on umbilical cord blood be closely monitored.